The Influence of The School Committee and The Principal's Leadership on The Quality of Education in Kindergartens in West Manokwari Sub-District - Malawat, Hawa; Yudha, Rivo Panji (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
This study aims to investigate the influence of the School Committee and the Principal's Leadership on the quality of education in kindergartens in West Manokwari District. This research uses field research, with the type of Quantitative research using a correlational approach. The instrument used is a questionnaire. In this study, the population and saturated samples taken were all parents of students in kindergartens in the West Manokwari sub-district, which had a population of 42 people and were used as saturated samples in this study as many as 42 people. Quantitative data analysis using IBM SPSS Statistics 22. Based on the results of the study, it was shown that, the probability number in the level of significance of 0.00 where the significant level α = 0.05 then H0 rejected Ha was accepted. This shows that there is an influence of the school committee and the principal's leadership on the Quality of Education In West Manokwari District. The result of the coefficient of determination in the regression model with an Adjusted R2 value of 0.691 can be interpreted that 69.1 percent of the quality of kindergarten education can be explained by the school committee and the leadership of the principal.